Effect of casting rate on the development of polysulfone flat sheet ultrafiltration membrane for the aluminium removal / Siti Hawa Rosli …[et al.] - Rosli, Siti Hawa; Mohd Tajuddin, Ramlah; Ab Rahim, Noor Raifana; Ismail, Siti Fatimah (2013)
This paper focused on the performance of flat sheet ultrafiltration membrane by various casting rate on the aluminium removal. Aluminium potassium sulfate (alum) known as an agent that used in water treatment processes to flocculate suspended particles but it may leave a residue of aluminium in the finished water. The removal of these impurities is significant based on its effect to human and environment. Therefore. membrane separation had developed in order to improve the method for removing the aluminium contaminants. The formulation of multicomponent (Polysulfone/poly(vinylpyrolidone)-K30/N.N dimethylacetamide ) flat sheet ultrafiltration membrane had developed using the dry/wet phase inversion technique. The membranes were produced at three different casting rate (11 m/min. 10 m/min, and 8.5 m/min) from controlled pressure of 90 psi. 70 psi and 50 psi. The performances of these membranes were tested by Salt (NaCl) rejection and also aluminium removal. Then, the morphology (skin layer and cross section) for each membrane was observed using Field Emission Scanning Electron Microscope (FESEM). From the experiments. it showed that casting rate directly influences both membrane morphology as well as membrane rejection performance. The highest percentage of sodium chloride (NaCl) rejection was observed from membrane fabricated at 11 m/min of casting rate with 42%. Moreover with the increment of casting rate. then the percentage aluminium removal also increased. As conclusion, from this study proved that casting rate influence significantly on the morphology, rejection and flux performance of flat sheet ultrafiltration membrane.